1980
DOI: 10.7589/0090-3558-16.2.233
|View full text |Cite
|
Sign up to set email alerts
|

EPIZOOTIOLOGY AND HISTOPATHOLOGY OF Chloromyxum trijugum (MYXOSPORA: MYXOSPORIDA) IN CENTRARCHID FISHES FROM IOWA

Abstract: Abstract:The gall bladder parasite, Chloromyxum trijugum, shows marked host specificity within the sunfish family Centrarchidae. During 1977-78 80% of 230 bluegills (Lepomis macrochirus) in Iowa were infected. Prevalence in green sunfish (L. cyanellus) was lower (17%); one of 2 specimens of the hybrid L. macrochirus X L. cyanellus was infected; orangespotted sunfish (L. humilis) and hybrids (L. humilis X L. macrochirus) were not infected. Intensity of infection in bluegills varied throughout the year. Prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1
1

Year Published

1987
1987
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
11
1
1
Order By: Relevance
“…In his description, Mitchell (1978) notes several features that are inconsistent with C. auratum, including large pigmented trophozoites and smaller spores with 15-16 ridged striae per valve. However, in a subsequent description of the parasite, the size of spore and number of ridges is less ) (see Table I).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In his description, Mitchell (1978) notes several features that are inconsistent with C. auratum, including large pigmented trophozoites and smaller spores with 15-16 ridged striae per valve. However, in a subsequent description of the parasite, the size of spore and number of ridges is less ) (see Table I).…”
Section: Discussionmentioning
confidence: 94%
“…More than 100 species of Chloromyxum have been described from marine and freshwater fishes (Lom and Dykova, 1993 Hoffman, 1999); C. trijugum (Xiao and Desser, 2000); C. truttae (Herrick, 1936;Mitchell et al, 1980;Mamyshev et al, 1981); Chloromyxum wardi, and Chloromyxum salamandrae (Upton et al, 1995); 4 marine species Chloromyxum ovatum (Jameson, 1929), Chloromyxum levigatum (Jameson, 1931), Chloromyxum kabatai (Moser and Noble, 1977), and Chloromyxum subsphaericum (Schulman, 1966;Moser and Noble, 1977); and several unidentified species (see Gowen, 1983;Kent et al, 1994;Hoff et al, 1997;Hoffman, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, the rather low intensity of infection prevented the collection of data on the developmental stages. Although Mitchell et al (1980) found the sporogonic plasmodia of C. trijugum attached to the gall-bladder wall, the early developmental stages should be looked for in the bile duct, as suggested by Davis (1985), who discovered plasmodia of the also gall-bladder parasite Zschokkella russeli in this site. In the case of parasites of this type, the presence of blood stages is unlikely, although Lom et al (1988) did not preclude this possibility.…”
Section: Discussionmentioning
confidence: 99%